Cyber-Attacks on Power System Frequency Control - Thongchart Kerdphol; N. Teera-achariyakul; Tossaporn Surinkaew; Watcharakorn Pinthurat (My University, 2024)
Due to the increasing number of cyber hacking activities, cyber-attacks become urgent concerns to power system security worldwide. A power system is vulnerable to cyber-attacks due to the exchanged information in its area. In this study, cyber-attacks on power system frequency control are studied by corrupting the exchange of information. Considering the frequency measurement of the system, essential attack strategies from hackers’ perspectives, which are usually concerned with cyber-attacks on critical infrastructure, have been modeled concerning the false data injection. Simulation results analyze the strengths and weaknesses of different attacks against frequency control of the system. The exogenous cyber-attacks on frequency power measurements can cause severe frequency excursions, which lead to system instability and power blackouts. Such attack methods require effective detection from defenders to guarantee system security before hackers further deteriorate the system’s stability.
Keywords: Smart Grid Security and Resilience; Network Security and Intrusion Detection